Evaluasi Pengawasan Otoritas Jasa Keuangan Terhadap Lembaga Keuangan Non-Bank: Studi Kasus SNP Finance - Tjoe Kang Long; Widyawati Boediningsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The case of PT Sunprima Nusantara Pembiayaan (SNP Finance) highlights the importance of effective supervision by the Financial Services Authority (OJK) of non-bank financial institutions in Indonesia. Through an evaluation of the case, this research addresses various aspects, including risk profile, corporate governance, profitability, and capitalization in the context of Non Performing Loan (NPL). It also reviews the legal aspects of the case, including violations of corporate law, criminal law, banking law, and auditor liability. The results suggest that increased supervision, the development of stricter regulations, better consumer education, and the use of technology in early detection could help prevent similar cases in the future.